THE IMPACT OF CORE RESOURCES AND TYPES OF STRATEGIC ALLIANCE ON ALLIANCES PERFORMANCE IN THE MALAYSIAN COMPANIES - Yajid, Mohd Shukri Ab (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to examine the ways Malaysian companies deal with strategic alliance and to identify the relationships between the resources and type of strategic alliance (strategic partners). Besides that, the objective of this research is to look into the influence of the resources, type of strategic alliance, coopetition of alliance member and key success factors onto the alliance performance. Indeed, the construction of this research depends on the exploration of these relationships, which induce the objectives of this research. The resource-based theory is applied to find out what are the phenomena of strategic alliance in the last five years. The coopetition relationship may affect the performance of alliance. How should companies assess the right type of alliance before partnering with others? What should be the factors leading to the success of alliance? From the empirical findings, many conclusions can be made. Firstly, there is a weak relationship between type of strategic alliances (strategic partners) and core resources. Secondly, the type of alliance has weak significance to alliance performance. Thirdly, there is no evidence to support the relationships between alliance performance and the type of coopetition. Next, the relationship between alliance performance and the key success factors is not supported. Besides that, the type of alliance has weak influence in the alliance performance while the relationship is controlled by coopetition. In addition, the weak effect of the relationships of alliance performance and type of alliance is controlled by the key success factors.